Medical students’ mental health status and coping strategies in their quarantine period during COVID-19 pandemic in Universiti Putra Malaysia - Abas, Razif; Minhat, Halimatus Sakdiah; Muhamad Saliluddin, Suhainizam; Basir, Rusliza; Ab Razak, Nur Izah; Mohamad Zainal, Nurul Hayati; Omar, Noorkardiffa Syawalina (Penerbit Universiti Sains Malaysia, 2021)
Movement control order (MCO) was enforced by the Malaysian government on 18th March 2020 due to sudden increase in the cumulative number of COVID-19 cases. University students, including medical students, were among the group of the population which were significantly affected. This study was conducted among medical students in Universiti Putra Malaysia (UPM) to compare the mental health status and coping strategies, between gender and phase of the clinical study related to their quarantine status between 18th March 2020 to 9th June 2020. This was a cross-sectional study involving the undergraduate medical students in UPM in the academic year of 2019/2020 during the MCO. A stratified random sampling method was used; a total of 173 respondents which includes students of Year 1 to Year 5 participated. The study was conducted after five months since the first day of MCO, for one week period of data collection. The mental health status was assessed using Depression, Anxiety and Stress Scale 21-item (DASS-21) questionnaire. Four-point Likert scale was scored to determine the degree of severity. The coping strategies was assessed using Brief-COPE (Coping Orientation to Problems Experienced) in which four-point Likert scale was used as well, and the total marks were grouped into four coping strategies. This study found higher scores of DASS-21 in the non-quarantined group and approach method was considered as a favourable coping strategy in both groups. In the quarantined group, female and clinical students showed higher scores of DASS-21. In the non-quarantined group, clinical students showed a significantly higher score of stress while male students significantly used their humour as coping strategies.